International tables of glycemic index and glycemic load values 2021: a systematic review - Atkinson, Fiona S; Brand-Miller, Jennie C; Foster-Powell, Kaye; Buyken, Anette; Goletzke, Janina (The American Journal of Clinical Nutrition)
ABSTRACT Background Reliable tables of glycemic indexes (GIs) and glycemic loads (GLs) are critical to research examining the relationship between glycemic qualities of carbohydrate in foods, diets, and health. In the 12 years since the last edition of the tables, a large amount of new data has become available. Objectives To systematically review and tabulate published and unpublished sources of reliable GI values, including an assessment of the reliability of the data. Methods This edition of the tables lists over 4000 items, a 61% increase in the number of entries compared to the 2008 edition. The data have been separated into 2 lists. The first represents more precise values derived using the methodology recommended by the International Standards Organization (∼2100 items). The second list contains values determined using less robust methods, including using limited numbers of healthy subjects or with a large SEM (∼1900 food items). Results Dairy products, legumes, pasta, and fruits were usually low-GI foods (≤55 on the 100-point glucose scale) and had consistent values around the world. Cereals and cereal products, however, including whole-grain or whole-meal versions, showed wide variation in GI values, presumably arising from variations in manufacturing methods. Breads, breakfast cereals, rice, savory snack products, and regional foods were available in high-, medium-, and low-GI versions. Most varieties of potato were high-GI foods, but specific low-GI varieties have now been identified. Conclusions The availability of new data on the GIs of foods will facilitate wider research and application of the twin concepts of GI and GL. Although the 2021 edition of the tables improves the quality and quantity of GI data available for research and clinical practice, GI testing of regional foods remains a priority. This systematic review was registered in PROSPERO as #171204.

Reply to Khan et al. - Schwingshackl, Lukas; Neuenschwander, Manuela; Hoffmann, Georg; Buyken, Anette; Schlesinger, Sabrina (The American Journal of Clinical Nutrition)

Dietary sugars and cardiometabolic risk factors: a network meta-analysis on isocaloric substitution interventions - Schwingshackl, Lukas; Neuenschwander, Manuela; Hoffmann, Georg; Buyken, Anette; Schlesinger, Sabrina (The American Journal of Clinical Nutrition)
ABSTRACT Background There is controversy on the relevance of dietary sugar intake for cardiometabolic health. Objective The aim of this network meta-analysis (NMA) was to assess how isocaloric substitutions of dietary sugar with other carbohydrates affect cardiometabolic risk factors, comparing different intervention studies. Methods We included randomized controlled trials (RCTs) investigating the isocaloric effect of substituting dietary sugars (fructose, glucose, sucrose) with other sugars or starch on cardiometabolic risk markers, including LDL cholesterol, triacylglycerol (TG), fasting glucose (FG), glycated hemoglobin (HbA1c), insulin resistance (HOMA-IR), uric acid, C-reactive protein (CRP), alanine transaminase (ALT), aspartate transaminase (AST), and liver fat content. To identify the most beneficial intervention for each outcome, random-effects NMA was conducted by calculating pooled mean differences (MDs) with 95% CIs, and by ranking the surface under the cumulative ranking curves (SUCRAs). The certainty of evidence was evaluated using the Confidence In Network Meta-Analysis tool. Results Thirty-eight RCTs, including 1383 participants, were identified. A reduction in LDL-cholesterol concentrations was shown for the exchange of sucrose with starch (MD: −0.23 mmol/L; 95% CI: −0.38, −0.07 mmol/L) or fructose with starch (MD: −0.22 mmol/L; 95% CI: −0.39, −0.05 mmol/L; SUCRAstarch: 98%). FG concentrations were also lower for the exchange of sucrose with starch (MD: −0.14 mmol/L; 95% CI: −0.29, 0.01 mmol/L; SUCRAstarch: 91%). Replacing fructose with an equivalent energy amount of glucose reduced HOMA-IR (MD: −0.36; 95% CI: −0.71, −0.02; SUCRAglucose: 74%) and uric acid (MD: −23.77 µmol/L; 95% CI: −44.21, −3.32 µmol/L; SUCRAglucose: 93%). The certainty of evidence was rated very low to moderate. No significant effects were observed for TG, HbA1c, CRP, ALT, and AST. Conclusions Our findings indicate that substitution of sucrose and fructose with starch yielded lower LDL cholesterol. Insulin resistance and uric acid concentrations were beneficially affected by replacement of fructose with glucose. Our findings are limited by the very low to moderate certainty of evidence. This review was registered at www.crd.york.ac.uk/prospero as CRD42018080297.

Relation of dietary glycemic index, glycemic load, added sugar intake, or fiber intake to the development of body composition between ages 2 and 7 y - Buyken, Anette; Cheng, Guo; Günther, Anke LB; Liese, Angela D; Remer, Thomas; Karaolis-Danckert, Nadina (The American Journal of Clinical Nutrition)

Effects of breastfeeding on health outcomes in childhood: beyond dose-response relations - Buyken, Anette; Karaolis-Danckert, Nadina; Günther, Anke; Kersting, Mathilde (The American Journal of Clinical Nutrition)

Dietary micronutrient intake during pregnancy is a function of carbohydrate quality - Goletzke, Janina; Buyken, Anette; Louie, Jimmy CY; Moses, Robert G; Brand-Miller, Jennie C (The American Journal of Clinical Nutrition)

WHO guidelines for a healthy diet and mortality from cardiovascular disease in European and American elderly: the CHANCES project - Jankovic, Nicole; Geelen, Anouk; Streppel, Martinette T; de Groot, Lisette CPGM; Kiefte-de Jong, Jessica C; Orfanos, Philippos; Bamia, Christina; Trichopoulou, Antonia; Boffetta, Paolo; Bobak, Martin; Pikhart, Hynek; Kee, Frank; et al. (The American Journal of Clinical Nutrition)

Association between carbohydrate quality and inflammatory markers: systematic review of observational and interventional studies - Buyken, Anette; Goletzke, Janina; Joslowski, Gesa; Felbick, Anna; Cheng, Guo; Herder, Christian; Brand-Miller, Jennie C (The American Journal of Clinical Nutrition)

The link between dietary glycemic index and nutrient adequacy - Louie, Jimmy Chun Yu; Buyken, Anette; Brand-Miller, Jennie C; Flood, Victoria M (The American Journal of Clinical Nutrition)

Consumption of polyunsaturated fatty acids, fish, and nuts and risk of inflammatory disease mortality - Gopinath, Bamini; Buyken, Anette; Flood, Victoria M; Empson, Marianne; Rochtchina, Elena; Mitchell, Paul (The American Journal of Clinical Nutrition)

Relation of isoflavones and fiber intake in childhood to the timing of puberty - Cheng, Guo; Remer, Thomas; Prinz-Langenohl, Reinhild; Blaszkewicz, Meinolf; Degen, Gisela H; Buyken, Anette (The American Journal of Clinical Nutrition)

Carbohydrate nutrition and inflammatory disease mortality in older adults - Buyken, Anette; Flood, Victoria; Empson, Marianne; Rochtchina, Elena; Barclay, Alan W; Brand-Miller, Jennie; Mitchell, Paul (The American Journal of Clinical Nutrition)

Body fat and animal protein intakes are associated with adrenal androgen secretion in children - Shi, Lijie; Wudy, Stefan A; Buyken, Anette; Hartmann, Michaela F; Remer, Thomas (The American Journal of Clinical Nutrition)

Birth and early life influences on the timing of puberty onset: results from the DONALD (DOrtmund Nutritional and Anthropometric Longitudinally Designed) Study - Karaolis-Danckert, Nadina; Buyken, Anette; Sonntag, Antje; Kroke, Anja (The American Journal of Clinical Nutrition)

Glycemic index in overweight development: distinguishing limited evidence from limits in evidence - Buyken, Anette; Günther, Anke LB; Barclay, Alan; Brand-Miller, Jennie; Schulze, Matthias B (The American Journal of Clinical Nutrition)

How pre- and postnatal risk factors modify the effect of rapid weight gain in infancy and early childhood on subsequent fat mass development: results from the Multicenter Allergy Study 90. - Karaolis-Danckert, N; Buyken, Anette; Kulig, M; Kroke, A; Forster, J; Kamin, W; Schuster, A; Hornberg, C; Keil, T; Bergmann, RL; Wahn, U; Lau, S (Am J Clin Nutr)

Association of prepubertal body composition in healthy girls and boys with the timing of early and late pubertal markers - Buyken, Anette; Karaolis-Danckert, Nadina; Remer, Thomas (The American Journal of Clinical Nutrition)

Association between long-term consumption of soft drinks and variables of bone modeling and remodeling in a sample of healthy German children and adolescents - Libuda, Lars; Alexy, Ute; Remer, Thomas; Stehle, Peter; Schoenau, Eckhard; Kersting, Mathilde (The American Journal of Clinical Nutrition)

Protein intake during the period of complementary feeding and early childhood and the association with body mass index and percentage body fat at 7 y of age. - Günther, AL; Buyken, Anette; Kroke, A (Am J Clin Nutr)

Breakfast glycemic index affects subsequent daily energy intake in free-living healthy children. - Buyken, Anette; Trauner, K; Günther, AL; Kroke, A; Remer, T (Am J Clin Nutr)

How early dietary factors modify the effect of rapid weight gain in infancy on subsequent body-composition development in term children whose birth weight was appropriate for gestational age. - Karaolis-Danckert, N; Günther, AL; Kroke, A; Hornberg, C; Buyken, Anette (Am J Clin Nutr)

Early protein intake and later obesity risk: which protein sources at which time points throughout infancy and childhood are important for body mass index and body fat percentage at 7 y of age? - Günther, AL; Remer, T; Kroke, A; Buyken, Anette (Am J Clin Nutr)

Rapid growth among term children whose birth weight was appropriate for gestational age has a longer lasting effect on body fat percentage than on body mass index. - Karaolis-Danckert, N; Buyken, Anette; Bolzenius, K; Perim de Faria, C; Lentze, MJ; Kroke, A (Am J Clin Nutr)

Glycemic index in the diet of European outpatients with type 1 diabetes: relations to glycated hemoglobin and serum lipids. - Buyken, Anette; Toeller, M; Heitkamp, G; Karamanos, B; Rottiers, R; Muggeo, M; Fuller, JH; IDDM Complications Study Group, EURODIAB (Am J Clin Nutr)